Health biotechnology in China: National, regional, and sectoral dimensions - Marcus Conlé (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2010)
Biotechnology is one of the knowledge fields particularly targeted by China, as it is considered to open up windows of opportunity for catch-up to the leading economies. However, the seizing of these opportunities requires the existence of an institutional and organizational structure supportive of the introduction and usage of biotechnological knowledge. The present contribution discusses this problem in its national, regional, and sectoral dimensions. By focusing on the biopharmaceutical sector, it is shown that the regulatory environment and the capital market constitute serious bottlenecks to further development.
Keywords: 330; China; health biotechnology; innovation system; pharmaceutical